Poison pen the true confessions of two tabloid reporters - Moskowitz-Mateu, Lysa; LaFontaine, David (Dove Books, 1996)
This no-holds-barred account of a husband-and-wife team of tabloid reporters will entertain with its high jinx and shock with its excesses. Lysa Moskowitz-Mateu and David LaFontaine spent one year traveling all over the continent as they chased down headline stories for the Star, the National Enquirer, and the Globe. By their own account, tabloid reporters are the "vermin media," and their outrageous quests for good interviews know no bounds. Read about racing in a hot-air balloon to catch a glimpse of the Liz Taylor-Larry Fortensky wedding, staying up all night in a hotel room next door to Whoopi Goldberg and Ted Danson and listening to the sounds of their love tryst, rushing to interview disaster victims and their families, and giving out false leads to other tabloid reporters in an effort to sabotage the competition, as well as being hot on the trail of dozens of celebrities including Kevin Costner, Lisa Marie Presley, Luke Perry, Nicole Kidman, John Travolta, Courteney Cox, Whitney Houston, and many more.